Rheology as a Tool to Investigate the Degradability of Hyaluronic Acid Dermal Fillers - Grimaldi G; Galasso G; Capillo MC; Alonci G; Bighetti S; Bettolini L; Sommatis S; Mocchi R; Carugno A; Zerbinati N (Clinical, Cosmetic and Investigational Dermatology, 2025)
Giulia Grimaldi,1 Giulia Galasso,1 Maria Chiara Capillo,1 Giuseppe Alonci,1 Stefano Bighetti,2 Luca Bettolini,2 Sabrina Sommatis,1 Roberto Mocchi,1 Andrea Carugno,3 Nicola Zerbinati4 1UB-CARE S.r.l.-Spin-Off, University of Pavia, Pavia, Italy; 2Dermatology Department, University of Brescia, ASST Spedali Civili di Brescia, Brescia, Italy; 3Department of Medicine and Surgery, University of Insubria, Varese, Italy; 4University of Insubria, Department of Medicine and Technology Innovation, Varese, ItalyCorrespondence: Stefano Bighetti, Dermatology Department, Piazzale Spedali Civili 1, Brescia, 25123, Italy, Tel +39 030 3995301, Fax +39 030 399505, Email s.bighetti@unibs.itBackground: In the current landscape of aesthetic medicine, the use of hyaluronic acid (HA)-based dermal fillers is increasingly prevalent. Although HA is widely acknowledged for its safety and efficacy the study of its degradability represents a critical aspect in ensuring safety.Methods: Rotational rheology was chosen to study the HA-based fillers interaction with hyaluronidase enzyme; this allows to establish a correlation between the viscoelastic parameters of the sample and its degradation.Results: The obtained results indicate that the products exhibit sensitivity to the enzyme and that the rheological parameters vary depending on the contact time and dosage of administration.Conclusion: Our findings propose a standardized rheological protocol for assessing the degradability of HA-based dermal fillers, offering an alternative to existing methods.Keywords: hyaluronic acid, adverse drug reaction, aesthetic dermatology, cosmetic dermatology